1999
DOI: 10.1086/314783
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Distinct Common Strain of “Norwalk‐like Viruses” Having a Global Distribution.

Abstract: "Norwalk-like viruses" (NLVs) are the most common cause of outbreaks of nonbacterial gastroenteritis. During molecular surveillance of NLV strains from 152 outbreaks of gastroenteritis that occurred in the US between August 1993 and July 1997, we identified an NLV strain that predominated during the 1995-1996 season. The "95/96-US" strain caused 60 outbreaks in geographically distant locations within the US and was identified, by sequence comparisons, in an additional 7 countries on 5 continents during the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
275
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 320 publications
(298 citation statements)
references
References 55 publications
21
275
2
Order By: Relevance
“…Similarly, the incidence of general practitioner consultations for norovirus was only slightly lower than that from a recent study in Germany, which used RT-PCR diagnosis for norovirus, but again this study had a narrower case definition for IID (2 or more loose stools, or 2 or more vomiting episodes in 24 hours) (21). The incidence of norovirus-associated IID may also have been higher than normal during our study because a new variant of norovirus emerged during 1995 and 1996 (22)(23)(24); emergence of norovirus variants has been associated with increased disease incidence (25)(26)(27)(28).…”
Section: Discussioncontrasting
confidence: 64%
“…Similarly, the incidence of general practitioner consultations for norovirus was only slightly lower than that from a recent study in Germany, which used RT-PCR diagnosis for norovirus, but again this study had a narrower case definition for IID (2 or more loose stools, or 2 or more vomiting episodes in 24 hours) (21). The incidence of norovirus-associated IID may also have been higher than normal during our study because a new variant of norovirus emerged during 1995 and 1996 (22)(23)(24); emergence of norovirus variants has been associated with increased disease incidence (25)(26)(27)(28).…”
Section: Discussioncontrasting
confidence: 64%
“…Recently, excretion of norovirus by symptomatic and asymptomatic individuals during a hospital outbreak of gastroenteritis where a GII/4 strain was dominant has been described (6). At present, norovirus GII/4 strains are the most prevalent in many countries (4,8,27,28). What is more, variant GII/4 sequences, i.e., those differing by approximately 5% of amino acids, were speculated to be more virulent and part of the reason for the increased number of infections worldwide (8).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, noroviruses have been detected in environmental samples (e.g., treated and untreated sewage) as well as in contaminated foods such as oysters, shellfish, sandwiches, salads, raspberries, and even ice (7,18,19,26). Numerous molecular epidemiological studies have revealed a global distribution of these viruses (25,27,31).The most widely used method of detecting noroviruses is reverse transcription-PCR (RT-PCR), which has high sensitivity; also, the products can be used for further genetic analysis. Real-time RT-PCR assays have also been developed; they are sensitive, broadly reactive, and rapid for the detection of human noroviruses in clinical stool specimens and environmental samples (13,14,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The members of the genera "Sapporo-like viruses" (SLVs) and "Norwalk-like viruses" (NLVs) in the family Caliciviridae [14,32] are an important cause of gastroenteritis in humans [4,8,10,12,21,28,30,39,40,43] and animals [7,15,26,38]. In humans, the illnesses caused by SLVs and NLVs differ in epidemiological features and clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%